Korelasi Indeks Massa Tubuh dan Pengetahuan Gizi terhadap Performa Kerja Guru Sekolah Dasar : Body Mass Index (BMI) and Nutritional Knowledge as well as the Correlation of Job Performance on Elementary School Teachers - Lestantyo, Daru; Denny, Hanifa Maher; Suroto, Suroto; Jayanti, Siswi; Cahyaningrum, Dwi (Universitas Airlangga, 2025)
Background: Nutritional knowledge and BMI have a significant impact on the health level of an individual. Elementary school teachers are part of the professional workforce with a relatively high administrative and academic workload. Teachers are expected to have good nutritional knowledge about eating habits and healthy lifestyle choices. Research conducted in Bogor found that 57.0% of teachers were indicated to have obesity. The better the level of knowledge, it is expected to have an impact on BMI, enabling teachers to be more productive and always in optimum health condition at work. Objectives: This research aimed to analyze the Body Mass Index (BMI) and nutritional knowledge correlation with job performance Methods: Approximately 40 teachers of private elementary schools were used with a cross-sectional method. All Participants were teachers of private elementary school. We interviewed and measured participants for age, and nutritional awareness. Individual Work Performance Questionnaire (IWPQ) adapted for Indonesians was used. Statistical analysis was carried out using statistics application with Rank-Spearman method. Meanwhile, BMI data were collected through the measurement of the height and weight of participants. Results: This research showed the correlation between BMI and Job Performance. A correlation between nutritional knowledge and job performance was also reported. Good nutritional knowledge of school teachers should be delivered to students to change eating habits. This variable could also affect healthy life and achievement levels. Conclusions: BMI and nutritional knowledge were correlated with job performance. Furthermore, teachers were expected to provide healthy lifestyle education subjects to the students.